Contextualization of Maslahah Jasser Auda’s Thought in Islamic Economy - Achmad Fageh (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
The Division of Maslahah can be deduced into five kinds, namely; (1) based on the purpose of the day/Time, (2) based on the level of necessity, (3) based on its coverage (range), (4) based on the presence or absence of changes and (5) based on the presence or absence of the Shariah in the assignment. Maslahah based on the purpose of his day divided into two levels, namely; Maslahah the world and the Hereafter.